Eruptive collagenoma: A rarely reported entity in Indian literature - Prachi Barad; Joycelin Fernandes; Pankaj Shukla (Wolters Kluwer Medknow Publications, 2015)
Eruptive collagenomas are non familial connective tissue nevi of unknown etiology presented with an abrupt onset. While most cases are reported in young adults, there is a paucity of literature in children. We report a case of a 4-year-old girl, who presented with multiple asymptomatic, papules, plaques and nodules on the face, trunk and upper extremities with no systemic involvement. Histopathologically, the lesion showed thickened homogenized collagen fibres highlighted by Masson's trichrome stain and paucity in elastic fibres by Verhoeff-van Gieson stain, confirming the diagnosis of eruptive collagenoma.